STABILITY INDICATING ULTRA PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD FOR SIMULTANEOUS DETERMINATION OF PHENYLEPHRINE HYDROCHLORIDE, CHLORPHENIRAMINE MALEATE, PARACETAMOL, GUAIPHENESIN AND BROMHEXINE HYDROCHLORIDE IN BULK AND PHARMACEUTICAL FORMULATION - CHENGALVA, PRASANTHI; KUCHANA, MADHAVI (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of the present study is to develop simple, rapid, sensitive, accurate and economic stability-indicating ultra-performance liquid chromatographic (UPLC) method for the simultaneous quantification of phenylephrine hydrochloride, chlorpheniramine maleate, paracetamol, guaiphenesin and bromhexine hydrochloride in bulk and tablet dosage form. Methods: The separation of drugs in the chromatographic column was accomplished on Hibar C18 (100 mm x 2.1 mm, 1.6 µm) column at a detection wavelength of 220 nm. The mobile phase was a combination of sodium phosphate monobasic monohydrate buffer (pH was adjusted to 3.5 with orthophosphoric acid) and acetonitrile in the ratio of 70:30 % v/v which was pumped at a flow rate of 0.3 ml/min. The column temperature was maintained at 30 °C and the injection volume was 0.3 µl. Forced degradation studies of drugs were carried out using acid, base, peroxide, light and heat. Results: All the five drugs have been eluted within 3 min. The retention times were found to be 0.834 min, 1.199 min, 1.600 min, 1.979 min and 2.525 min for phenylephrine, chlorpheniramine maleate, paracetamol, guaiphenesin and bromhexine respectively. The correlation coefficient (r2) was found to be 0.999 for all the drugs. The recovery levels were found to be in the range of 99.17 % to 100.69 %. RSD values of drugs were found to be below 2 %. The results of limit of detection and quantitation specified the sensitivity of the developed method. Significant degradation of drugs as a result of stress studies was found in acid, base and peroxide, but they were slightly degraded in photolytic and thermal conditions. The method has effectively resolved the degraded products. All the validation parameters were found to be within the limits according to International Conference on Harmonization (ICH) guidelines. Conclusion: A simple and rapid UPLC method was established for the determination of five drugs. Hence, the proposed method can be employed for the quality control of specified drugs in bulk and pharmaceutical formulation even in the presence of degradation products.